2022
DOI: 10.4103/jfmpc.jfmpc_2219_21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increased screen time on eyes during COVID-19 pandemic

Abstract: Purpose: The objective of the study was to assess the effect of increased screen time on ocular health during the coronavirus disease (COVID-19) crisis. Materials and Method: An online pretested, self-reported questionnaire with relevant details was generated through Google form and sent to participants. Chi-square or Fisher’s exact test was used to investigate the associations between the qualitative variables. The associated risk factors of number and frequency of ocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Prior to the COVID-19 pandemic, a study had shown 30% of all eating occasions occurring at non-designated eating places, such as with a screen or watching television ( 32 ). The high prevalence of eating occasions with screens in this study was not surprising as studies have shown significant increases in screen time and digital device use during the COVID-19 lockdown period across the globe ( 33 , 34 ). Research from nine European countries involving 4,108 participants found a 65% increase in screen time during the pandemic ( 33 ).…”
Section: Discussionmentioning
confidence: 59%
“…Prior to the COVID-19 pandemic, a study had shown 30% of all eating occasions occurring at non-designated eating places, such as with a screen or watching television ( 32 ). The high prevalence of eating occasions with screens in this study was not surprising as studies have shown significant increases in screen time and digital device use during the COVID-19 lockdown period across the globe ( 33 , 34 ). Research from nine European countries involving 4,108 participants found a 65% increase in screen time during the pandemic ( 33 ).…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, red eyes constituted 14.3%, swollen eyes constituted 13% and dry eyes constituted 8%. Similarly, eye problems caused by the increased screen time use have been reported in literature (Agarwal, Tripathi, Khan & Agarwal, 2022;Al-Mohtaseb, Schachter, Shen Lee, Garlich & Trattler, 2021;Maroof, et al, 2019;Shantakumari, Eldeeb, Sreedharan & Gopal, 2014).…”
Section: Findings and Discussionmentioning
confidence: 74%
“… 12 The frequency and severity of dry eyes and headaches also increased. 13 Moreover, VDT working hours among wage workers greatly increased compared to before the pandemic, resulting in an increase in the number of wage workers who experienced eyestrain. 13 14 15 In this study, 14.4% of the non-VDT work group experienced headache/eyestrain, whereas 27.5% of the VDT work group experienced the symptoms.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Moreover, VDT working hours among wage workers greatly increased compared to before the pandemic, resulting in an increase in the number of wage workers who experienced eyestrain. 13 14 15 In this study, 14.4% of the non-VDT work group experienced headache/eyestrain, whereas 27.5% of the VDT work group experienced the symptoms. The risk of headache/eyestrain in the group who always used VDT was 2.21 times higher than that in the group who never used VDT.…”
Section: Discussionmentioning
confidence: 99%